An Overview of Emotional Intelligence by Using ASYIK Rewards in Group B of Pulogadung 01 State Kindergarten - Sri Endah Wahyuningsih; Sri Watini (Journal of Childhood Development, 2024)
The emotional intelligence abilities of young children in the Pulogadung 01 State Kindergarten group were improved using the School's Reward ASYIK method. This research was conducted to determine the role of the ASYIK Reward method in developing and cultivating the emotional intelligence abilities of young children at the Pulogadung 01 State Kindergarten. The type of research carried out in this thesis is using a qualitative descriptive method with research that presents several facts and problems that occur in the field. The data collection technique in this research uses several techniques such as observation, interviews, and documentation collection. The results of the data analysis process carried out in this research were based on the ASYIK reward method in group B, which develops children's emotional intelligence at an early age at the Pulogadung 01 State Kindergarten. With these Rewards, the teaching and learning process and emotional intelligence can increase children's enthusiasm in competing to get prizes which can have an influence on the development of children's emotional intelligence.